1994
DOI: 10.3109/07420529409057237
|View full text |Cite
|
Sign up to set email alerts
|

Time Dependency in the Regenerative Response to Injury of the Rat Corneal Epithelium

Abstract: In the present study a central corneal epithelial defect (diameter 3.5 mm) was made in both eyes at 12:00 h in one group of rats and at 24:00 h in another group to see if the regenerative proliferation is influenced by circadian rhythms. The labeling index and the mitotic rate were registered at 4-h intervals in the perilimbal conjunctiva, the limbal area, and different parts of the cornea from the following morning until noon the day after that. The most pronounced regenerative proliferation was seen in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…Based on this hypothesis, corneal epithelial mitosis is a core factor that maintains corneal epithelial integrity and homeostasis. In the present study, we showed diurnal changes in normal mouse corneal mitosis, which was in accordance with previous studies showing that corneal mitosis and DNA synthesis exhibit circadian oscillations associated with the changes in light during the day and night161718. However, the diabetic condition decreased the circadian rhythm of corneal epithelial mitosis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Based on this hypothesis, corneal epithelial mitosis is a core factor that maintains corneal epithelial integrity and homeostasis. In the present study, we showed diurnal changes in normal mouse corneal mitosis, which was in accordance with previous studies showing that corneal mitosis and DNA synthesis exhibit circadian oscillations associated with the changes in light during the day and night161718. However, the diabetic condition decreased the circadian rhythm of corneal epithelial mitosis.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, circadian rhythms influence generative processes after wounding55. Corneal wounding at different times of the day reveals that the regenerative response of the corneal epithelium to injury is time-dependent18. Moreover, epithelial proliferation is significantly altered56.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The central co-ordinating pacemaker is located in the suprachiasmatic nucleus (SCN) of the hypothalamus. Amongst the many genes influenced by circadian rhythms are those involved in cell cycle and even in the context of a wound environment can be found evidence of diurnal variation of mitotic activity [18], [19]. Whilst it is not possible within the framework of the present study to determine whether circadian rhythms influence mitotic activity following physical airway injury there is currently wider interest in the observation that airway diseases such as asthma are characterised by dyssynchrony in epithelial mitotic responses following injury [20].…”
Section: Discussionmentioning
confidence: 94%
“…Conjunctival and limbal values of LI were also higher on the 1st day for group B and on the 2nd day for both groups, but with very low MR. One reason might be that the cells are entering mitosis at another time of the day. This is, however, unlikely since the mitotic activity has been shown to be highest at the time of the day these observations were made, due to the diurnal variation (Sandvig et al 1994). Another explanation might be that the cells have migrated more centrally before entering mitosis.…”
Section: Discussionmentioning
confidence: 99%